2016
DOI: 10.1080/15592294.2016.1145330
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide methylation analysis of retrocopy-associated CpG islands and their genomic environment

Abstract: Gene duplication by retrotransposition, i.e., the reverse transcription of an mRNA and integration of the cDNA into the genome, is an important mechanism in evolution. Based on whole-genome bisulfite sequencing of monocyte DNA, we have investigated the methylation state of all CpG islands (CGIs) associated with a retrocopy (n D 1,319), their genomic environment, as well as the CGIs associated with the ancestral genes. Approximately 10% of retrocopies are associated with a CGI. Whereas almost all CGIs of the hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…In this study, we employed pyrosequencing at 18 CpG rich UCNEs to determine the pattern of methylation conservation using 56 representative species covering 300–400 million years of evolution. We expected DNA methylation at UCNEs to be either near 0% or near 100%, since the overwhelming majority of CpG sites within the genome exhibit one of these maxima [ 30 ]. Unexpectedly, we found that several UCNEs exhibited intermediate DNA methylation consistently across their embedded CpG sites.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we employed pyrosequencing at 18 CpG rich UCNEs to determine the pattern of methylation conservation using 56 representative species covering 300–400 million years of evolution. We expected DNA methylation at UCNEs to be either near 0% or near 100%, since the overwhelming majority of CpG sites within the genome exhibit one of these maxima [ 30 ]. Unexpectedly, we found that several UCNEs exhibited intermediate DNA methylation consistently across their embedded CpG sites.…”
Section: Discussionmentioning
confidence: 99%
“…Placenta samples were obtained from the Institute of Molecular Biology/Department of Gynecology and Obstetrics, University Hospital Essen, Germany after informed consent. 21 First trimester placenta samples (Placenta 1-3) were taken at week 9, 10 and 11 of gestation, respectively, after abortions that were not medically indicated. Third trimester placenta samples (Placenta 4 and 5) were taken after the birth of healthy babies at week 36 and 37 of gestation.…”
Section: Materials and Methods Samplesmentioning
confidence: 99%
“…For subsequent data analysis the Amplikyzer software was used. 21 Only reads with a conversion rate over 95% were considered.…”
Section: Dna Methylation Analysis Of the Meg8-dmr Meg3-dmr And Ig-dmmentioning
confidence: 99%
“…Methylation analysis of the CUL7 DMR described by Hamada et al (2016) was conducted in DNA from blood of normal controls, three first and three third-term placenta samples (Grothaus et al 2016) (Beygo et al, submitted; maternal contamination was excluded before) by next-generation bisulfite sequencing on the Roche/454 GS junior system (Branford, CT, USA) as described previously (Beygo et al 2013) using tagged primers F1 5 0 -CTTGCTTCCTGGCACGAG-GGGTAGGGTGTATAG ATTAGGTAGG-3 0 with R1 5 0 -CAGGAAACAGCTAT GAC-CCCTTACTCTATAAAAAACAAACCTC-3 0 and F2 5 0 -CTTGCTTCCTGGCACGAG-GAGGTTTGTTTTTTATA GAGTAAGGGA-3 0 with R2 5 0 -CAGGAAACAGCTATGAC-TCCAAAATCTTTTCCAATTCTAACTT-3 0 .…”
Section: Molecular Testingmentioning
confidence: 99%